Landmark-Centric Routing for Wireless Sensor Networks in Mobile Delay Tolerant Environments. (16th June 2014) - Chen, Jiaxu; Tang, Yazhe; Hu, Chengchen; Li, Xun; Wang, Huanzhao
Wireless sensor networks (WSNs) have wide applications in many fields sharing common grounds as their major technical challenges. This paper focuses on a high-level information association issue and designs an efficient routing protocol accordingly for delay tolerant mobile sensor networks (DTMSNs). In this paper, after making an analysis about the effect of social network theory on forwarding scheme and node mobility, we exploit landmark, a new social-aware metric indicating the geographical location corresponding to a node interest or a node community. To the best of our knowledge, this is the first work in which landmark is utilized to assist message forwarding in DTMSNs. Additionally, we propose the landmark-centric routing protocol utilizing the metric to accurately predict node mobility geographically. We can take full advantage of node mobility in our protocol while preserving the positive effects of existing social-aware metrics on protocol performance. Simulation results show that the proposed protocol achieves the highest packet delivery ratio outperforming SocialCast and doubling SGBR with more than 50% delivery cost reducing.